Endometrial polyps. An evidence-based diagnosis and management guide. (May 2021) - Vitale, Salvatore Giovanni; Haimovich, Sergio; Laganà, Antonio Simone; Alonso, Luis; Di Spiezio Sardo, Attilio; Carugno, Jose; ,
Abstract: Objective: To provide an updated practice guideline for the management of patients with endometrial polyps. Materials and Methods: A committee of six expert researchers draw the recommendations according to AGREE II Reporting Guideline. An electronic search was performed querying the following databases MEDLINE (accessed through PubMed), Scopus, PROSPERO, EMBASE, CINAHL, Cochrane Library (including the Cochrane Database of Systematic Reviews), Scielo.br, Google Scholar, from inception to May 2020. A combination of text-words and Medical Subject Headings (MeSH) regarding endometrial polyps, diagnosis, management and treatment was used. Trials were assessed for methodologic rigor and graded using the United States Preventive Services Task Force classification system. Recommendations: Transvaginal ultrasonography (TVUS) should be the imaging modality of choice for the detection of endometrial polyps in woman of fertile age (level B). Its accuracy increases when color-doppler, 3D investigation and contrast are used (level B). Dilation and Curettage (D&C) should be avoided for the diagnosis and management of polyps (level A). In office hysteroscopy showed the highest diagnostic accuracy in infertile patients with suspected endometrial polyps (level B). Polyps might alter endometrial receptivity, and embryo implantation reducing pregnancy rates (level C). Hysteroscopic polypectomy is feasible and safe with negligeble risk of intrauterine adhesion formation (level B). Polypectomy does not compromise reproductive outcomes from subsequent IVF procedures but the removal of polyps as a routine practice in sub-fertile women is not currently supported by the evidence (level B). Cost-effectiveness analysis suggest performing office polypectomy in women desiring to conceive (level B). Saline infused sonohysterography is highly accurate in detecting polyps in asymptomatic postmenopausal women (level B). Postmenopausal women with vaginal bleeding and suspected endometrial polyp should be offered diagnostic hysteroscopy with hysteroscopic polypectomy if endometrial polyps are present (level B). In-office hysteroscopy has the highest diagnostic accuracy with high cost-benefits ratio for premalignant and malignant pathologies of the uterine cavity (level B). Due to risk of malignancy, histopathological analysis of the polyp is mandatory (level B). Blind D&C should be avoided due to inaccuracy for the diagnosis of focal endometrial pathology (level A). Expectant management is not recommended in symptomatic patients especially in postmenopausal women (level B). In case of atypical hyperplasia or carcinoma on a polyp, hysterectomy is recommended in all post-menopausal patients and in premenopausal patients without desire of future fertility (level B). Asymptomatic endometrial polyps in postmenopausal women should be removed in case of large diameter (> 2 cm) or in patients with risk factors for endometrial carcinoma (level B). Excision of polyps smaller than 2 cm in asymptomatic postmenopausal patients has no impact on cost-effectiveness or survival (level B). Removal of asymptomatic polyps in premenopausal women should be considered in patients with risk factors for endometrial cancer (level B).